Analisis Tingkat Kepuasan Peserta Pelatihan AutoCAD Online untuk Pengabdian Masyarakat Terdampak Covid-19 dengan Metode Kirkpatrick Level I - Madi Madi; Yoyok Setyo Hadiwidodo; Tuswan Tuswan; Abdi Ismail (Jurnal Pengabdian Pada Masyarakat, 2020)
SATISFACTION LEVEL ANALYSIS OF AUTOCAD ONLINE TRAINING PARTICIPANTS FOR COMMUNITY SERVICE AFFECTED BY COVID-19 USING KIRKPATRICK LEVEL I METHOD. Online AutoCAD training is an activity to learn modelling techniques using AutoCAD software for participants affected by Covid-19. Online AutoCAD training was held to increase people's productivity during the pandemic, increase knowledge, and develop modelling ability using AutoCAD software. The number of participants registered to join this program was 49 participants from open recruitment which consisted of 59% male participants and 41% female participants. The program ran for four meetings online, each session 1.5 hours with a system of introduction, learning, assignments, and exams. The service team also provides free facilitators, facilities, presenters and materials (F2PM) for training participants. So, to find out participants' satisfaction, it is necessary to conduct an evaluation at the end of the training. The review was carried out by means of an online survey to the participants, then processed qualitatively with the Kirkpatrick Level I method. The final result of the participant evaluation of the facilitator was considered acceptable (59%), the facilities were considered excellent (67%), the presenters were considered very good (56 %), and the material is considered very good (59%). In the future, evaluation data on the level of participant satisfaction can be used as a recommendation and motivation to organize advanced training.